Slow recovery in temperate mesophotic communities following disturbance: An example from Lough Hyne (Ireland) - Valerio Micaroni; Rob McAllen; Alberto Rovellini; Francesca Strano; Christine Morrow; Bernard Picton; John Turner; Luke Harman; James J. Bell (Marine Environmental Research, 2025)

Pointed‐snout wrasse builds nest on Sarcotragus foetidus sponges - Francesca Strano; Francesco Tiralongo; Valerio Micaroni (Ecology, 2025)

Spatial variation in the rocky temperate benthic mesophotic communities of the Wellington region in New Zealand - James J. Bell; Francesca Strano; Manon Broadribb; Ben Harris; Alice Rogers; Valerio Micaroni (New Zealand Journal of Marine and Freshwater Research, 2024)
Temperate mesophotic ecosystems (TMEs) have only recently been recognised as distinct ecosystems and generally occur between 30 and 150 m at the limit of photosynthetic light penetration. In this study, we surveyed the benthic communities inhabiting rocky deep‐water features in two regions at the south of New Zealand's North Island to assess small (1–2 km) and larger (10–100 km) scale variation in the benthic communities they support: the Wellington South Coast (WSC) and the Kāpiti Coast (KC). We deployed Remotely Operated Vehicles at seventeen sites, three on the WSC and 14 on the KC, covering a depth range of 26 to 72 m. There was significant variation in the benthic community composition between sites, at both spatial scales, and with depth. Across all sites, sponges and bryozoans were by far the most abundant organisms, covering around 30% of the substrate, with all other groups having

Nature-based solutions for monitoring the impact of vehicular particulate matter and for the preventive conservation of the Palatine Hill archaeological site in Rome, Italy - Lisa Grifoni; Aldo Winkler; Francesca Boldrighini; Luigi Antonello Di Lella; Alfonsina Russo; Antonio Sgamellotti; Lilla Spagnuolo; Gabriella Strano; Stefano Loppi (Science of The Total Environment, 2024)

Marine heatwave‐driven mass mortality and microbial community reorganisation in an ecologically important temperate sponge - James J. Bell; Valerio Micaroni; Francesca Strano; Ken G. Ryan; Katherine Mitchell; Paul Mitchell; Shaun Wilkinson; Torsten Thomas; Ramadian Bachtiar; Robert O. Smith (Global Change Biology, 2024)
Marine heatwaves (MHWs) are increasing in frequency, duration and intensity, disrupting global marine ecosystems. While most reported impacts have been in tropical areas, New Zealand experienced its strongest and longest MHW in 2022, profoundly affecting marine sponges. Sponges are vital to rocky benthic marine communities, with their abundance influencing ecosystem functioning. This study examines the impact of this MHW on the photosynthetic sponge Cymbastella lamellata in Fiordland, New Zealand. We describe the extent, physiological responses, mortality, microbial community changes and ecological impact of this MHW on C. lamellata . The Fiordland MHW reached a maximum temperature of 4.4°C above average, lasting for 259 days. Bleaching occurred in >90% of the C. lamellata Fiordland population. The population size exceeded 66 million from 5 to 25 m, making this the largest bleaching event of its kind ever recorded. We identified the photosynthetic symbiont as a diatom, and bleached sponges had reduced photosynthetic efficiency. Post‐MHW surveys in 2023 found that over 50% of sponges at sampling sites had died but that the remaining sponges had mostly recovered from earlier bleaching. Using a simulated MHW experiment, we found that temperature stress was a driver of necrosis rather than bleaching, despite necrosis only rarely being observed in the field ( C. lamellata are key contributors of dissolved organic carbon to the water column, with their loss likely impacting ecosystem function. We demonstrate the potential for MHWs to disrupt key marine phyla in temperate regions, highlighting how susceptible temperate sponges globally might be to MHWs.

Could spatial variation be more important than species identity in determining the presence of microplastics in temperate sponges? - Rachel L. Parry; Valerio Micaroni; Francesca Strano; James J. Bell (New Zealand Journal of Marine and Freshwater Research, 2024)
Microplastic (MP) particles ( ‐1 (dry sponge weight). There were significant differences in PMP abundance between sites and between some species, but most of the variation was explained by site (40–53% vs. 4–24% of the variance). Our results suggest that PMP abundance in sponges is mainly explained by spatial variation in microplastic abundance rather than species identity.

Global status, impacts, and management of rocky temperate mesophotic ecosystems - James J. Bell; Valerio Micaroni; Benjamin Harris; Francesca Strano; Manon Broadribb; Alice Rogers (Conservation Biology, 2024)
The ecology and function of rocky temperate mesophotic ecosystems (TMEs) remain poorly understood globally despite their widespread distribution. They typically occur at 20–150 m (the limit of photosynthesis), and on rocky substratum they support rich benthic communities and mobile fauna. We determined the distribution of rocky TMEs, their conservation status, and their most characteristic biological groups. Rocky TMEs were dominated by algae, turf‐invertebrate matrices (

Morphological diversity and a ribosomal phylogeny of Rhabdopleura (Hemichordata: Graptolithina) from the Western Pacific (Singapore and New Zealand), with implications for a re-evaluation of rhabdopleurid species diversity - Dennis P. Gordon; Z. B. Randolph Quek; Russell J. S. Orr; Andrea Waeschenbach; Danwei Huang; Francesca Strano; Mali H. Ramsfjell; Lee Hsiang Liow (Marine Biodiversity, 2023)
The recent discovery of Rhabdopleura in Singapore and the chance collecting of fresh material from northern New Zealand (Three Kings Shelf) provided an opportunity to sequence the specimens with an aim to determine their species identity. Phylogeny reconstructions of two new Rhabdopleura taxa based on ribosomal and mitochondrial genes suggest a different identity from known samples, including putative Rhabdopleura annulata , first described from the Three Kings Shelf but sequenced from the Great Barrier Reef. Pairwise distances between rhabdopleurids for the 16S rRNA locus were several magnitudes larger than that of 18S rRNA, and might potentially be a suitable barcoding gene once sufficient samples of conspecifics are collected to determine the barcoding gaps. Type material of R. annulata was re-examined, as well as Rhabdopleura material from eight other New Zealand localities from north of subtropical Raoul Island (Kermadec Ridge) at ~29° S to the subantarctic Campbell Plateau at ~49° S. Six morphological characters, four of them new, were applied to all samples. The findings from morphology suggest (1) the holotype and cotype of R. annulata might not be conspecific; (2) there are 3–4 variants (species?) on the Three Kings Shelf; and (3) there are 2–3 additional variants (species?) elsewhere in the New Zealand region.

Adaptive strategies of sponges to deoxygenated oceans - Valerio Micaroni; Francesca Strano; Rob McAllen; Lisa Woods; John Turner; Luke Harman; James J. Bell (Global Change Biology, 2022)
Ocean deoxygenation is one of the major consequences of climate change. In coastal waters, this process can be exacerbated by eutrophication, which is contributing to an alarming increase in the so‐called ‘dead zones’ globally. Despite its severity, the effect of reduced dissolved oxygen has only been studied for a very limited number of organisms, compared to other climate change impacts such as ocean acidification and warming. Here, we experimentally assessed the response of sponges to moderate and severe simulated hypoxic events. We ran three laboratory experiments on four species from two different temperate oceans (NE Atlantic and SW Pacific). Sponges were exposed to a total of five hypoxic treatments, with increasing severity (3.3, 1.6, 0.5, 0.4 and 0.13 mg O 2 L −1 , over 7–12‐days). We found that sponges are generally very tolerant of hypoxia. All the sponges survived in the experimental conditions, except Polymastia crocea , which showed significant mortality at the lowest oxygen concentration (0.13 mg O 2 L −1 , lethal median time: 286 h). In all species except Suberites carnosus , hypoxic conditions do not significantly affect respiration rate down to 0.4 mg O 2 L −1 , showing that sponges can uptake oxygen at very low concentrations in the surrounding environment. Importantly, sponges displayed species‐specific phenotypic modifications in response to the hypoxic treatments, including physiological, morphological and behavioural changes. This phenotypic plasticity likely represents an adaptive strategy to live in reduced or low oxygen water. Our results also show that a single sponge species (i.e., Suberites australiensis ) can display different strategies at different oxygen concentrations. Compared to other sessile organisms, sponges generally showed higher tolerance to hypoxia, suggesting that sponges could be favoured and survive in future deoxygenated oceans.

Shallow-water sponge grounds along the Apulian coast (central Mediterranean Sea) - Francesca Strano; Valerio Micaroni; Gabriele Costa; Iacopo Bertocci; Marco Bertolino (Marine Biodiversity, 2020)

Project “Biodiversity MARE Tricase”: biodiversity research, monitoring and promotion at MARE Outpost (Apulia, Italy) - Valerio Micaroni; Francesca Strano; Davide Di Franco; Joachim Langeneck; Cinzia Gravili; Marco Bertolino; Gabriele Costa; Fabio Rindi; Carlo Froglia; Fabio Crocetta; Adriana Giangrande; Luisa Nicoletti; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)